Transformando uma muralha em fronteira: a conexão do Vale do Paraíba do Sul ao litoral no Brasil oitocentista - Santa Cruz de Assis Brasil, Lucas; Oliveira, Rogério R. (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2021)
Abstract Communication between productive areas and ports was of extreme importance in the colonial system. Cattle cars, on smaller slopes, and mules’ troops, used on more rugged terrain, were the primary means of transporting goods during colonization. The creation, maintenance, and use of roads produced changes in the landscape noticeable until the present day. The Serra da Bocaina, a geographical accident between the port of Mambucaba and the Paraíba do Sul River Valley, is an emblematic example of the changes generated by human agents crossing the mountain range with mules’ troops towards the coast. The opening of tracts in the forest centuries ago for rest and animal feed has altered the biota of some portions of the mountain, replacing the previously existing flora with areas of open vegetation composed of exotic and native grasses and herbaceous. The "Bocaina Fields" can be interpreted as ecological results of the stumbling in the Serra do Mar, a geographical phenomenon that highlights the hidden work in the landscape, observable in the vegetation physiognomy of such areas.